Effectivity of glutathione and curcumin in hepatic fibrosis induced by cholestasis in Wistar rats - Rodijaya Putra; Adeodatus Yuda Handaya; Agus Barmawi (Intisari Sains Medis, 2021)
Background: Cholestasis occurs from the accumulation of bile product in the biliary tract due to obstruction of the hepatobiliary tract. Without early interventions, this condition will be continuing as chronic hepatic injury and form hepatic fibrosis, ending in cirrhosis. Glutathione (GSH) and curcumin were known as antioxidants and anti-inflammatory used as a therapeutic agent for the treatment of hepatopathy. This study aims to determine the effectivity of GSH and curcumin in the hepatic fibrosis mechanism induced by cholestasis. Methods: This is an experimental study using Wistar rats. They are divided into three groups of 5 rats each. All the rats regard the choledochus duct ligation surgery, rats without intervention define as first group (control), other rats treated with GSH as the second group and the third group consist of rats treated with curcumin. Data were analyzed using SPSS version 17 for Windows.Results: There was liver injury and hepatic fibrosis induced by cholestasis from this study. This condition was significantly lower in groups treated with GSH and curcumin (p<0.05). Therefore, there was a different result between GSH and curcumin in reducing the process of liver injury and hepatic fibrosis, but the difference was not statistically significant (p>0.05).Conclusion: GSH and curcumin were statistically effective in reducing liver injury and hepatic fibrosis induced by cholestasis. Despite, there were no significant difference results between them in reducing liver injury and hepatic fibrosis.